Identification of Mycobacterium species by using amplified ribosomal DNA restriction analysis. - Vaneechoutte, M (1993)
A rapid procedure for the identification of cultured Mycobacterium isolates, based on the combination of enzymatic amplification and restriction analysis, is described. The 16S rRNA genes (rDNA) of 99 strains belonging to 18 different species of the genus Mycobacterium were enzymatically amplified. Amplified rDNA restriction analysis with the enzymes CfoI, MboI, and RsaI was carried out. The combination of the amplified rDNA restriction analysis patterns obtained after restriction with CfoI and MboI enabled differentiation between Mycobacterium asiaticum (number of strains = 4), M. avium (n = 22), M. chelonae (n = 5), M. flavescens (n = 1), M. fortuitum (n = 6), M. gordonae (n = 6), M. intracellulare (n = 13), M. marinum (n = 7), M. nonchromogenicum (n = 1), M. simiae (n = 5), M. terrae (n = 5), the M. tuberculosis complex (n = 11), and 2 of 4 strains of M. xenopi. Further restriction with RsaI was necessary to differentiate between the species M. kansasii (n = 5), M. scrofulaceum (n = 4), and the 2 other M. xenopi strains. The M. avium-M. intracellulare complex was characterized by a specific MboI pattern, and M. avium and M. intracellulare strains could further be differentiated by restriction with CfoI. The whole procedure, including sample preparation prior to the polymerase chain reaction, can be carried out within 8 h, starting from a pure culture.